2002
DOI: 10.1592/phco.22.3.175.33546
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Levofloxacin During Continuous Venovenous Hemodiafiltration and Continuous Venovenous Hemofiltration in Critically Ill Patients

Abstract: Marked extracorporeal elimination of levofloxacin occurs, requiring a dosage adjustment that can be calculated from the characteristics of CVVH and CVVHDF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 32 publications
1
15
0
1
Order By: Relevance
“…However, as discussed below, protein binding in the critically ill is variable and for some drugs (e.g. levofloxacin) S c varies widely [24][25][26][27][28] . Furthermore, S c may be affected by membrane material, drug-membrane interactions and flux properties.…”
Section: Pharmacokinetic Factorsmentioning
confidence: 99%
“…However, as discussed below, protein binding in the critically ill is variable and for some drugs (e.g. levofloxacin) S c varies widely [24][25][26][27][28] . Furthermore, S c may be affected by membrane material, drug-membrane interactions and flux properties.…”
Section: Pharmacokinetic Factorsmentioning
confidence: 99%
“…[27]. This levofloxacin CL NR in the previous study was reported to be much higher than all of those reported in other published studies with similar patient population receiving CRRT (mean range of 15.0-30.9 mL/min) ( Table 5) [31][32][33][34]. Sensitivity analyses evaluated the influence of different PIRRT operation settings on PTA of fluoroquinolone dosing regimens.…”
Section: Discussionmentioning
confidence: 72%
“…Body weight was derived from a large PIRRT study [4] and pharmacokinetic data from published ciprofloxacin and levofloxacin pharmacokinetic studies in critically ill patients receiving RRT [29][30][31][32][33][34][35][36]. In order to avoid spurious simulations, limits were obtained from those previous studies and were set for all input parameters.…”
Section: Pharmacokinetic Model Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…7 The information presented in its monographs is derived from pertinent references in the literature and expert therapeutic guidelines. 7 Notwithstanding the increasing body of literature concerning pharmacokinetic alterations during (Maintenance Dosage) Acyclovir 5-10 mg/kg IV NR 5-10 mg/kg IV q12-24h 5-10 mg/kg IV q24h q12-24h 6,18 Amikacin 5-7.5 mg/kg IV 4.5-10.5 mg/kg per day NR 7.5 mg/kg IV q24-72h q24-48h 6,19,20 IV divided q12-18h Amoxicillin 1000 mg PO q6h 19,21 NR NR NR Amphotericin, lipid complex 5 mg/kg IV q24h Imipenem-cilastatin 500 mg IV q6-8h 6,45 500 mg IV q6-8h 500 mg IV q6-8h 500 mg IV q6h Levofloxacin 250-750 mg IV/PO NR 250-750 mg IV/PO q24h 500 mg IV/PO q48h q24h 6,32,46 Linezolid 600 mg IV/PO q12h 47,48 NR NR 600 mg IV/PO q12h Meropenem 500-1000 mg IV 1000 mg IV q12h 500 mg IV q6-12h or 1000-2000 mg IV q12h q8-12h 6,[49][50][51][52][53][54][55][56] 1000 mg IV q8-12h Metronidazole 500 mg IV q6-12h 6,21 500 mg IV q6-12h NR 250-500 mg IV q8-12h Moxifloxacin 400 mg IV/PO q24h NR NR 3.1 g IV q8-12h Tobramycin 1-2.5 mg/kg IV 0.3-1.75 mg/kg 1-2.5 mg/kg IV q24-48h 1.7 mg/kg IV q24-48h q24-48h 6,19 IV q12h ‡ Vancomycin 7.5-15 mg/kg IV 500 mg IV q24-48h or 10-15 mg/kg IV 1000 mg IV q24-96h § q12-48h 6,37,[65][66][67][68][69] 1000 mg IV q48h § q24-48h or 7.5-10 mg/kg IV q12h Voriconazole 400 mg PO q12h × 2, NR No adjustment needed; 100% usual dosage then 200 mg PO q12h 13,…”
Section: Discussionmentioning
confidence: 99%